A multidisciplinary study of archaeological grape seeds - Cappellini, Enrico (Springer-Verlag, 2009)
We report here the first integrated investigation of both ancient DNA and proteins in archaeobotanical samples: medieval grape (Vitis vinifera L.) seeds, preserved by anoxic waterlogging, from an early medieval (seventh–eighth century A.D.) Byzantine rural settlement in the Salento area (Lecce, Italy) and a late (fourteenth–fifteenth century A.D.) medieval site in York (England). Pyrolysis gas chromatography mass spectrometry documented good carbohydrate preservation, whilst amino acid analysis revealed approximately 90% loss of the original protein content. In the York sample, mass spectrometry-based sequencing identified several degraded ancient peptides. Nuclear microsatellite locus (VVS2, VVMD5, VVMD7, ZAG62 and ZAG79) analysis permitted a tentative comparison of the genetic profiles of both the ancient samples with the modern varieties. The ability to recover microsatellite DNA has potential to improve biomolecular analysis on ancient grape seeds from archaeological contexts. Although the investigation of five microsatellite loci cannot assign the ancient samples to any geographic region or modern cultivar, the results allow speculation that the material from York was not grown locally, whilst the remains from Supersano could represent a trace of contacts with the eastern Mediterranean. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00114-009-0629-3) contains supplementary material, which is available to authorized users.